Re-Epithelialization Appraisal of Skin Wound in a Porcine Model Using a Salmon-Gelatin Based Biomaterial as Wound Dressing - Cristian A. Acevedo; Elizabeth Sánchez; Nicole Orellana; Patricio Morales; Yusser Olguín; Donald I. Brown; Javier Enrione (MDPI AG, 2019)
The design of new functional materials for skin tissue engineering is an area of constant research. In this work, a novel wound-dressing biomaterial with a porous structure, previously formulated using salmon-gelatin as main component (called salmon-gelatin biomaterial (SGB)), was tested in vivo using pigs as skin wound models. Four weeks after cutaneous excision and implantation in the animals, the healing process did not show apparent symptoms of inflammation or infection. Interestingly, the temporal evolution of wound size from 100% to around 10% would indicate a faster recovery when SGB was compared against a commercial control. Histological analysis established that wounds treated with SGB presented similar healing and epithelialization profiles with respect to the commercial control. Moreover, vascularized granulation tissue and epithelialization stages were clearly identified, indicating a proliferation phase. These results showed that SGB formulation allows cell viability to be maintained. The latter foresees the development of therapeutic alternatives for skin repair based on SGB fabricated using low cost production protocols.